Cumulative years in occupation and the risk of hip or knee osteoarthritis in men and women: a register-based follow-up study. Issue 5 (11th January 2012) - Andersen, Susan; Thygesen, Lau Caspar; Davidsen, Michael; Helweg-Larsen, Karin
Abstract : Objectives: Occupational workload has been associated with an increased risk of osteoarthritis (OA), but only little research has been conducted among female workers. The objective of this study was to analyse if men and women in farming, construction or healthcare work have increased risk of developing OA of the hip or knee. Methods: A follow-up study based on register data of the whole Danish working population in the period 1981 to 2006 followed up for hip or knee OA during 1996 to 2006. Cumulative years in occupation were calculated for assessment of dose–response relationship. Gender-specific analyses were carried out with Cox regression models using age as timescale and adjusting for calendar period, income, unemployment and previous knee injury, and done separately for hip and knee OA. Results: Male floor layers and bricklayers and male and female healthcare assistants had the highest risks of knee OA, and farmers had the highest risk of hip OA. Male farmers had increased risk of hip OA already after 1–5 years in occupation (HR, 1.63) and a dose–response-related risk of hip OA (HR up to 4.22). Generally, the risk of OA increased with cumulative years in the occupation in both men and women. Conclusions: Occupations with heavy physical workload present a strong risk for hip and knee OA in both men and women, and the risks increase with cumulative years in occupation and noticeable hip OA among male farmers.